Meningkatkan Literasi Teks Berita Melalui Aplikasi Berita Digital: Studi Berbasis Kelas Tentang Keterlibatan Membaca Siswa - Chofifah Diah Nur Aliyah; Laila Tri Lestari; Anisa Ulfah (Universitas KH. Abdul Chalim Pacet Mojokerto, 2025)
The low interest in reading among students remains a major challenge in learning Indonesian, particularly in news text material that requires skills in understanding and writing factual information. This study aims to explore the use of the digital news application Opera News in news text learning as an effort to enhance students’ reading interest and writing skills. The research employed a qualitative approach with a Classroom Action Research (CAR) design, carried out in three reflective cycles. Data were collected through observation, questionnaires, documentation, and interviews. The findings indicate an increase in students’ engagement with digital news reading, active participation in classroom discussions, and comprehension of news text structures and content. Students’ news writing skills also improved in terms of content, text organization, and language use. The integration of Opera News into learning activities made literacy practices more contextual, interactive, and aligned with students’ digital habits. These results highlight that the use of digital media can be an effective strategy to foster reading interest and enhance students’ literacy skills. The study recommends the sustainable integration of digital news applications in Indonesian language learning to support adaptive literacy development in line with the demands of the digital era.